(untitled) - Nieto, Sonia (Mahwah, N.J., 2002)
Nieto (U. of Massachusetts) presents this textbook for current and future teachers facing an increasingly-diverse student population. Coverage includes ways in which language, culture and learning are linked in educational settings; the sociocultural and sociopolitical aspects of language and culture; the implications of linguistic and cultural diversity for school reform and educational equity; and ways for practicing and preservice teachers to reflect critically on their classroom practices in relation to linguistic and cultural diversity.
Keywords: Multicultural education,Minorities; Education; United States,United States